The moderating role of parental sleep knowledge on children with developmental disabilities and their parents' sleep - Halstead, Elizabeth J. (2021)
Background: Children with intellectual and developmental difficulties often experience sleep problems, which in turn may impact parental sleep patterns. This study explored the role of parental sleep knowledge as a moderator on the relationship between child sleep and parental sleep impairment. Methods: 582 parents or caregivers (92.6% mothers) of children with different developmental disabilities (Age M = 9.34, 29.5% females) such as Down’s syndrome, participated in an online survey. Multiple regression analysis was conducted. Results: Parental sleep knowledge of child sleep was a moderating variable in the relationship between child sleep nocturnal duration and parental sleep impairment. Although overall, sleep knowledge was high in this sample, two specific knowledge gaps were identified namely child sleep duration requirements, and the recognition of signs of a well-rested child. Conclusion: This study has provided evidence that increased parental sleep knowledge can positively impact both child and parental sleep outcomes